2019
DOI: 10.1016/j.heliyon.2019.e01129
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of temperature effect on antioxidant activity, phenolic compounds and color of Iranian jujube honey

Abstract: In the present study, the Iranian jujube honey was evaluated for its total antioxidant activity by DPPH assay, total phenolic content (TPC) by using the Folin–Ciocalteu reagent, and brown pigment formation (BPF). The kinetics of changes in jujube honey samples heated at various temperatures (45, 55 and 65 °C) over 10 days were studied. Increasing treatment temperature and time caused an increase in all three parameters including, antioxidant activity, BPF and TPC. Increases in BPF and TPC followed zero-order k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 39 publications
(55 reference statements)
4
31
0
1
Order By: Relevance
“…We used seven temperatures in our experiment, allowing us to notice the behavior of the roasting process; when Taoukis et al [56] states that five or six experimental temperatures are the practical optimum to obtain meaningfully narrow confidence limits in kinetic parameters (E a and k). The values obtained from the fitted parameters in Matlab are given in Table 2 and consistent with previous studies [26,28,41,57], in which the first-order kinetic model explains both TPC and epicatechin degradation at all temperatures; the k value of epicatechin is higher than the k value of TPC. These results suggest that the degradation of epicatechin is faster than the degradation of TPC.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We used seven temperatures in our experiment, allowing us to notice the behavior of the roasting process; when Taoukis et al [56] states that five or six experimental temperatures are the practical optimum to obtain meaningfully narrow confidence limits in kinetic parameters (E a and k). The values obtained from the fitted parameters in Matlab are given in Table 2 and consistent with previous studies [26,28,41,57], in which the first-order kinetic model explains both TPC and epicatechin degradation at all temperatures; the k value of epicatechin is higher than the k value of TPC. These results suggest that the degradation of epicatechin is faster than the degradation of TPC.…”
Section: Discussionsupporting
confidence: 86%
“…Fitting procedures (Matlab 2014) were used to determine the reaction rate constants for TPC, epicatechin, and catechin. The general kinetic models of zero-, first-, and second-order reactions were used, presented in Equations (2)-(4), respectively [41].…”
Section: Experimental Desing For Kinetics Of Tpc and Monomeric Flavanmentioning
confidence: 99%
“…Furthermore, the chromatogram of phenolic components divulged that the concentrations of gallic acid, ferulic, epicatechin, catechin, and p‐coumaric derivatives among others were high in HEVCO compared to CEVCO (Srivastava et al, ). Authors reasoned that high temperatures during the hot process of VCO production could improve the incorporation of high phenolic substances (Marina, Man, & Amin, ; Molaveisi, Beigbabaei, Akbari, Noghabi, & Mohamadi, ; Seneviratne & Sudarshana Dissanayake, ; Srivastava et al, ). Contrarily, Ghani et al () reported that TPC of VCO from wet process such as fermentation (12.54 ± 0.96 mg GAE/g) was high compared to the dry processing during hot process evaporates excess moisture in coconut milk emulsion (VCO‐Hot) improving the incorporation of phenolics (Mulyadi, Schreiner, & Dewi, ).…”
Section: Resultsmentioning
confidence: 99%
“…The method described by Molaveisi, Beigbabaei, Akbari, Noghabi, and Mohamadi () was slightly modified and then used to determine the DPPH (2,2‐diphenyl‐1‐picrylhydrazyl) radical scavenging activity. In brief, 0.5 mL of jujube honey dissolved in warm water and 1.5 mL of 0.1 mM DPPH (Sigma) were mixed in methanol.…”
Section: Methodsmentioning
confidence: 99%